Adiponectin and chronic kidney disease; a review on recent findings - Heidari Maryam; Nasri Parto; Nasri Hamid (Society of Diabetic Nephropathy Prevention, 2015)
Adiponectin is a multifunctional cytokine that has a role in regulating inflammation. In patients without chronic renal failure (CRF) and type 2 diabetics, decreased adiponectin levels are associated with insulin resistance. Lower serum plasma adiponectin values are link to larger tumor size and metastasis in clear-cell carcinoma of the kidney too. However, in patients with established chronic kidney disease (CKD), adiponectin levels are elevated and positively predict progression of disease. In addition, increased levels of serum adiponectin of hemodialysis patients were associated with decrease in bone mineral density in hemodialysis patients. Thus, depending on type of renal failure should be adjusted the adiponectin levels in patients. In CKD patients without diabetic, decreasing adiponectin levels by ARB drugs may be appropriate for inhibition of disease progression.